Challenges in Human Resource Management and Organisational Development in the Arabian Gulf: An Analysis of National Identity and Diversity - Randeree, K (Common Ground, 2008)
Middle Eastern economies generally lag behind global competitors. The United Arab Emirates (UAE) is no exception, as it faces many challenges including future demographics, employment of its national workforce, sustainability issues, educational concerns, as well as diversity and gender related problems. In truth, a well designed Emiratisation process (a policy for reducing the demand for expatriate workers) coupled with the active participation of Emirati women in mainstream society, including the private sector, can help in alleviating many of the UAE’s problems. The challenge for the rulers of the UAE, is to engage its national human resource in education and employment whilst moving in step with advanced nations and respecting Arab and Islamic tradition. Thus, due in part to the advancement and comparatively liberal nature of the UAE in comparison to other countries on the peninsula, the international community looks to the UAE, and the city of Dubai in particular, as a model for a new, prosperous and sustainable 21st century Middle East. The implications of the research presented here are that there are a number of challenges facing Emirati society and by implication the Arabian Gulf region, which need to be addressed if change and advancement envisaged by the region is to be realised.